Barbulifer enigmaticus, a new seven-spined goby (Pisces: Teleostei: Gobiidae) from the southwestern Atlantic - Joyeux, Jean-Christophe; van Tassell, James L.; Macieira, Raphael Mariano (Zootaxa, 2009)
A new Barbulifer species is described from 26 specimens. Barbulifer enigmaticus differs from its congeners by the following combination of characters: body completely lacks scales, including modified basicaudal scales. Cephalic pore pattern generally B’FH’ + M’O’ in juveniles and B’FH’ + M’NO’ in adults. No median barbel on snout. A single short barbel on each side of head, flattened, flexible, and located between the eye and the upper jaw, directly below the anterior nostril. A single median pair of short barbels on chin. D1 VII, D2 13(12–13), A 11(10–11), P 19(18–20). To 24 mm SL (29 mm TL). The species is found in very shallow reef areas from Espírito Santo to São Paulo, southeastern Brazil.